An evaluation of approaches for quantifying emissions from indirect land use change - Ruth Delzeit; Gernot Klepper; Mareike Söder (Kiel Institute for the World Economy (IfW), 2016)
The contribution of biofuels to save greenhouse gas emissions has been challenged over the last years. A still unresolved question is how to quantify emissions from indirect land use change (iLUC). In this paper we review approaches to quantify iLUC-emissions. We conclude that economic simulation models have fewer drawbacks compared to two other approaches. We find that economic simulation models contain a high level of uncertainty with respect to key model parameters. Further, we conclude that it is inappropriate to calculate crop-specific iLUC-emissions and to include them into binding regulation. We argue that modelling results, particularly crop-specific ones, should not be used for policy decisions.
Keywords: C61; Q16; Q42; 330; CGE Modeling; indirect land use change; biofuels; greenhouse gas emissions